Faktor Yang Mempengaruhi Deteksi Dini Resiko Tinggi Kehamilan - Prafitri, Lia; Suparni; Nur Intan Kusuma (Poltekkes Kemenkes Riau, 2025)
Early detection of a high risk of pregnancy is crucial to prevent serious complications for the mother and fetus. However, the main challenge in pregnant women's health services in various regions is the low early detection rate. Factors such as education level, knowledge about pregnancy health, and access to health services are suspected to affect low awareness and preventive measures in pregnant women. This study aims to analyze the influence of these factors on the early detection of pregnancy risk using a cross-sectional quantitative approach with 103 pregnant women at the Tirto I Health Center, Pekalongan Regency, through a chi-square test. The findings showed a significant relationship between knowledge level (p-value 0.001), education (p-value 0.021), and health insurance ownership (p-value 0.017) on early detection of pregnancy risk. It is hoped that health workers can improve education and access to services to improve early detection of pregnancy risks.